Relationship of Average Outcomes Scores and Change in Status Requires Further Interpretation Between 1 and 2 Years Following Hip Arthroscopy. Issue 12 (October 2022) - McGovern, Ryan P.; Martin, RobRoy L.; Christoforetti, John J.; Disantis, Ashley E.; Kivlan, Benjamin R.; Wolff, Andrew B.; Nho, Shane J.; Salvo, John P.; Van Thiel, Geoffrey S.; Matsuda, Dean K.; Carreira, Dominic S.
Background: Previous studies have demonstrated a clinically impactful change in patients between 1 and 2 years after hip arthroscopy. Assessment of differences in patient-specific factors between patients who remain the same and those who change (ie, either improve or decline) could provide valuable outcome information for orthopaedic surgeons treating those patients. Purpose: To identify patients who experienced change in functional status between 1 and 2 years after hip arthroscopy for femoroacetabular impingement syndrome and assess differences in patient-specific factors between those who improved, remained the same, or declined in functional status. Study Design: Cohort study; Level of evidence, 3. Methods: Prospectively collected data for patients who underwent hip arthroscopy at 1 of 7 centers were analyzed retrospectively at 1 year and 2 years postoperatively. Patients were categorized as "improved, ""remained the same, " or "declined" between 1- and 2-year follow-up based on the 12-item International Hip Outcome Tool (iHOT-12) minimal clinically important difference (MCID) value. A 1-way analysis of variance was used to assess differences in iHOT-12 scores, age, body mass index (BMI), alpha angle, and center-edge angle (CEA) between groups. Chi-square analyses were used to assess differences in the proportions of male and female patients in the outcome groups. Results: The study included 753 patients (515 women and 238 men), whose mean ± SD age was 34.7 ± 12 years. Average 1-year (±1 month) and 2-year (±2 months) iHOT-12 scores for all patients were 73.7 and 74.9, respectively. Based on the calculated MCID of ±11.5 points, 162 (21.5%) patients improved, 451 (59.9%) remained the same, and 140 (18.6%) declined in status between 1- and 2-year follow-up. Those who improved between 1 and 2 years had lower 1-year iHOT-12 scores ( P < .0005). We found no difference in age, BMI, alpha angle, CEA, or sex between groups ( P > .05). Conclusion: Between 1- and 2-year follow-up assessments, 21.5% of patients improved and 18.6% declined in self-reported functional status. Those with iHOT-12 scores indicating abnormal function at 1 year improved beyond the MCID at 2 years follow-up. Thus, any decisions about the failure or success of arthroscopic hip procedures should not be made until at least the 2-year follow-up. Failing to thrive at 1-year follow-up may not accurately predict outcomes at year 2 or beyond. This could potentially decrease the perceived need for revision surgery in patients who do not thrive before 2-year follow-up.